Masculinity, Competence, and Health: The Influence of Weight and Race on Social Perceptions of Men. (October 2013) - Trautner, Mary Nell; Kwan, Samantha; Savage, Scott V.
Like other visible characteristics such as skin color, gender, or age, body size is a diffuse status characteristic that impacts perceptions, interactions, and social outcomes. Studies demonstrate that individuals hold preconceived notions about what it means to be fat and document a long list of negative stereotypes associated with fat individuals, including laziness, unintelligence, and incompetence. Such perceptions have consequences for employment, including decisions about hiring, promotion, compensation, and dismissal. In this article, we examine how body size and race interact to affect individuals' perceptions of success, competence, health, laziness, and masculinity. Based on undergraduate students' ratings of photographs of men, our findings demonstrate significant differences between evaluations of black and white men based on body size. Thin white men are perceived to be more intelligent, more successful, and more competent than their thin black counterparts. However, these results reverse when the men are overweight: overweight black men are seen as more intelligent and more competent than overweight white men. They are also seen as more successful and hardworking and more masculine. These results suggest that the stigma of body size differently impacts black and white men; individuals judge overweight white men more negatively than overweight black men. We discuss two possible explanations for these findings: black threat neutralization and race-based attribution theory.